2015
DOI: 10.1016/j.brainres.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Repair of spinal cord injury with neuronal relays: From fetal grafts to neural stem cells

Abstract: Spinal cord injury (SCI) disrupts the long axonal tracts of the spinal cord leading to devastating loss of function. Cell transplantation in the injured spinal cord has the potential to lead to recovery after SCI via a variety of mechanisms. One such strategy is the formation of neuronal relays between injured long tract axons and denervated neurons. The idea of creating a neuronal relay was first proposed over 25 years ago when fetal tissue was first successfully transplanted into the injured rodent spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…FSC tissue has been used as a cellular resource for spinal cord repair [30,31]. Our results demonstrated that FSC-derived Table 1 The body weight and respiratory behavior of unanesthetized rats before and after transplantation grafts can fill the lesion cavity and survive in the injured spinal cord for at least 8 weeks.…”
Section: Survival Of Fsc Graftsmentioning
confidence: 74%
“…FSC tissue has been used as a cellular resource for spinal cord repair [30,31]. Our results demonstrated that FSC-derived Table 1 The body weight and respiratory behavior of unanesthetized rats before and after transplantation grafts can fill the lesion cavity and survive in the injured spinal cord for at least 8 weeks.…”
Section: Survival Of Fsc Graftsmentioning
confidence: 74%
“…Cell grafting after SCI has a long history comprehensively reviewed elsewhere (161,162). In humans, anatomically complete lesions are dominated by large non-neural lesion cores ( Figure 1C and ref.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…These strategies are primarily directed towards promoting repair of the damage and/or minimising the secondary injury processes. [33] Besides several invasive and pharmacological management strategies, we selected to study the influence of ELF-MF exposure in SCI rats. ELF-MF has the advantage of being non-invasive, non-pharmacological and simple to administer management strategy.…”
Section: Discussionmentioning
confidence: 99%